2018
DOI: 10.1039/c8cc01663a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient white-light emission in a polar two-dimensional hybrid perovskite

Abstract: Broadband white-light emission was realized in a polar two-dimensional hybrid perovskite, (2meptH2)PbBr4 (2mept = 2-methyl-1,5-diaminopentane). The white-light emission originates from self-trapped excitons owing to the distortion-induced polar structure. Notably, it exhibits a high photoluminescence quantum efficiency of 3.37% and an ultrahigh colour rendering index of 91.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 40 publications
5
89
0
Order By: Relevance
“…2b). 32,[50][51][52] Recently, M. D. Smith et al rationalized the structure/optical properties relationship by examining the ratio between the intensities of the broad emission (I BE ) and the narrow emission (I NE ) in a set of eight <100>-oriented bromide perovskites. 47,53 Within this dataset, it was found that the relative intensity of the broad emission (given by the ratio I BE /I NE ) increases with the increase of out-of-plane distortion of the Pb-(µ-Br)-Pb angle, with the exception of (CEA) 2 PbBr 4 (CEA = cyclohexylammonium) which shows room temperature broadband emission despite the absence of out-of-plane tilt.…”
Section: Broadband Emission In Low Dimensional Perovskitesmentioning
confidence: 99%
“…2b). 32,[50][51][52] Recently, M. D. Smith et al rationalized the structure/optical properties relationship by examining the ratio between the intensities of the broad emission (I BE ) and the narrow emission (I NE ) in a set of eight <100>-oriented bromide perovskites. 47,53 Within this dataset, it was found that the relative intensity of the broad emission (given by the ratio I BE /I NE ) increases with the increase of out-of-plane distortion of the Pb-(µ-Br)-Pb angle, with the exception of (CEA) 2 PbBr 4 (CEA = cyclohexylammonium) which shows room temperature broadband emission despite the absence of out-of-plane tilt.…”
Section: Broadband Emission In Low Dimensional Perovskitesmentioning
confidence: 99%
“…[6][7][8][9] Among the low-dimensional perovskites, two-dimensional (2D) layered crystals have been the focus of several studies, given their bright emission, possible white fluorescence, and, in particular, their environmental stability. [10][11][12][13][14] Moreover, 2D perovskites have exciton binding energies of about 300 meV that are larger than those of their 3D counterparts, which is advantageous for potential applications in the field of optoelectronics. [15][16][17] Layered perovskite crystals are made of a sequence of inorganic layers formed by corner-sharing [PbX 6 ] 4− octahedra, which are chemically passivated by organic moieties with smaller dielectric constant and higher exciton binding energies than the inorganic layer.…”
Section: Introductionmentioning
confidence: 99%
“…Stable 2D organic–inorganic hybrid halide perovskites with white emissions and high color tunability which are also low‐cost and easy‐process are promising single‐component phosphor material for light emitting diodes (LEDs). [ 22–26 ] As the 2D organic–inorganic hybrid perovskites have achieved tunable narrow emission recently, broadband white light emissions are observed in a few (110)‐oriented organic–inorganic hybrid 2D corrugated perovskites. Such as ( N ‐MEDA)[PbBr 4 ] ( N ‐MEDA = N 1 ‐methylethane‐1,2‐diammonium) [ 22 ] and α‐(DMEN)PbBr 4 (DMEN = 2(dimethylamino)ethylammonium) [ 24 ] are typical corrugated (110)‐oriented 2D perovskites for warm white‐light emission.…”
Section: Introductionmentioning
confidence: 99%